The generalized heat function - Greatbatch, R; Zhai, X (2007)
A generalized heat function is defined for diagnosing the pathways by which heat is carried by the ocean. In contrast to previous work, our generalized heat function varies along an isentrope only in the presence of mixing. The generalized heat function is diagnosed using the Levitus global ocean data set, net northward heat transport based on the data set of Grist and Josey, and different specifications for mixing in the ocean. The separation between the heat flux carried by the shallow wind driven cells and the deep overturning circulation is clearly revealed, with up to 0.4 PW being associated with the spreading of North Atlantic Deep Water. The importance of eddy-induced mixing near the surface of the Southern Ocean is evident. Copyright 2007 by the American Geophysical Union.